Dispatches contestations and celebrations on the Filipino heritage consciousness - Sembrano, Edgar Allan M. (España, Manila, Philippines University of Santo Tomas Publishing House, 2021)
“The Heritage dispatches evidenced by the dynamism of culture is vital contribution to societal development. The celebrations and contestations were needed to encourage reflections on practices, assessment of policies, and promote critical thinking that would endanger theory. In the end, values were formed and reformed which upheld heritage sensitivity and cultural respect. It may be perceived as a collection of sporadic events but the continuity of vigilance and commitment to conservation make heritage the essence of humanity.”-–Eric Zerrudo, from the Foreword.
Chapter 1: Threats and sweet treats -- Chapter 2: Storied but sorry -- Chapter 3: Meaningful gatherings -- Chapter 4: More questions than answers -- Chapter 5: Cultural renaissance and defiance -- Chapter 6: Rediscovery and memory -- Chapter 7: Landmark decision -- Chapter 8: Prevent but allow -- Chapter 9: Changes and vestiges -- Chapter 10: Winning, losing.
Includes bibliographical references (pages 452-453) and index.
Keywords: Cultural property -- Philippines; Historic preservation -- Philippines; Philippines -- Cultural policy; Philippines -- Social life and customs -- 21st century